ANALYSIS OF CONCRETE PROJECT COST CALCULATIONS IN PT. EVA MAHKOTA PURA SORONG - Menik Wijayanti; Tri Harjanti (LPPM Politeknik Saint Paul Sorong, 2018)
Cost of production is a very important thing considering the benefits of information on the cost of production is to determine the selling price of products that will be presented with statements of financial position. The purpose of this research is to analyze the calculation of the cost of goods used at PT. Eva Mahkota Pura. The company did not include plastiment and sikament as auxiliary raw materials on factory overhead costs, so factory overhead costs according to the company calculation of factory overhead costs amounted to Rp 101,759,026, while after analysis by the author produced Rp 106,928,475. Thus the difference in the amount of Rp 5,169,449.